Transcriptional Regulation of Structural and Functional Adaptations in a Developing Adulthood Myocardium - Sunny, Sini; Challa, Anil Kumar; Qiao, Aijun; Jyothidasan, Arun; Krishnamurthy, Prasanna; Ramamurthy, Muralidharan T; Crossman, David K; Pogwizd, Steven; Cinghu, Senthilkumar; Rajasekaran, Namakkal S (Cardiology and Cardiovascular Medicine, 2021)
The development of the heart follows a synergic action of several signaling pathways during gestational, pre- & postnatal stages. The current study aimed to investigate whether the myocardium experiences transcriptional changes during the transition from post-natal to adulthood stages. Herein, we used C57/Bl6/J mice at 4 (28- days; post-natal/PN) and 20 weeks (adulthood/AH) of ages and employed the next generation RNAseq (NGS) to profile the transcriptome and echocardiography analysis to monitor the structural/functional changes in the heart. NGS-based RNA-seq revealed that 1215 genes were significantly upregulated and 2549 were down regulated in the AH versus PN hearts, indicating a significant transcriptional change during this transition. A synchronized cardiac transcriptional regulation through cell cycle, growth hormones, redox homeostasis, and metabolic pathways was noticed in both PN and AH hearts. Echocardiography revealed significant structural and functional (i.e. systolic/diastolic) changes during the transition of PN to adult stage. Particularly, a progressive decline in ejection fraction and cardiac output was observed in AH hearts. These structural adaptations are in line with critical signaling pathways that drive the maturation of heart during AH. Overall, we have presented a comprehensive transcriptomic analysis along with a structural-functional relationship during the myocardial development in adult mice.